Ultra-low moisture high-wetting separator and method of making same
Patent Information
- Application Number
- CN202311441562.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-01
AI Technical Summary
[0003]PP和PE为非极性高分子,电解液浸润性较差,进而导致电池内阻较大,加之其孔隙率较低(约40%)而带来的低离子电导率,因而会严重限制电池的大倍率性能,难以满足电池大电流快速充放电的需要,无法解决隔膜当前面临的问题,也无法满足高性能隔膜的市场需求
[0027]1.本发明在隔膜表面使用勃姆石纤维和碳酸酯的混合物进行表面改性,可以有效提高隔膜低水分能力进而提高热稳定性能以及阻燃性和浸润性,提升电池安全性,从而提高电池耐久度,进而提高新能源电动汽车的续航能力;
Smart Images

Figure CN117374518B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery separator technology, specifically relating to an ultra-low moisture, high wetting separator, its preparation method, and its application. Background Technology
[0002] With the development of the times, new energy electric vehicles have gradually become an integral part of people's lives. As the power source of electric vehicles, the safety and range of lithium-ion batteries are the focus of scientific research. Lithium battery separators play an important role in lithium-ion batteries.
[0003] PP and PE are non-polar polymers with poor electrolyte wettability, which leads to high internal resistance in the battery. In addition, their low porosity (about 40%) results in low ionic conductivity, which severely limits the high-rate performance of the battery. This makes it difficult to meet the needs of high-current rapid charging and discharging of the battery, and cannot solve the current problems faced by the separator, nor can it meet the market demand for high-performance separators. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing ultra-low moisture and highly wettable slurry.
[0005] Another object of the present invention is to provide a membrane with ultra-low moisture and high wettability.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned ultra-low moisture and highly wettable membrane.
[0007] The objective of this invention is achieved through the following technical solution.
[0008] A method for preparing an ultra-low moisture, highly wettable slurry includes the following steps:
[0009] S1, Boehmite fiber and coupling agent are mixed at 70-75°C and stirred for 30-35 minutes to obtain a semi-finished product. The semi-finished product is then filtered, dried, pulverized and sieved to obtain a first mixture, wherein the coupling agent is carbonate.
[0010] In S1, the drying process involves drying to a moisture content of 0.6–0.8 wt%.
[0011] In S1, the boehmite fibers have a length of 200-250 mm and a diameter of 3-4 μm.
[0012] S2, mix the first mixture, dispersant and water, stir until uniform, and sonicate to obtain the first solution;
[0013] In S2, the frequency of the ultrasound is 50–75 kHz, and the duration of the ultrasound is 10–15 min.
[0014] In S2, the rotation speed of the stirring is 3100-3600 r / min, the revolution speed of the stirring is 10-30 r / min, and the stirring time is 10-15 min.
[0015] In S2, the dispersant is an ammonium salt dispersant.
[0016] S3, the adhesive and the first solution are ultrasonically mixed and milled under stirring conditions to obtain an ultra-low moisture high wetting slurry, wherein, by mass parts, the ratio of boehmite fiber, dispersant, coupling agent, water and adhesive is (23-25):(0.1-0.2):(0.04-0.08):(37-39):(1-3).
[0017] In S3, the adhesive is a polyacrylate adhesive.
[0018] In S3, the polyacrylate adhesive is a mixture of water-based polyacrylate adhesive and heat-resistant polyacrylate adhesive, and the ratio of water-based polyacrylate adhesive to heat-resistant polyacrylate adhesive by mass is (3-6):(1-2).
[0019] In S3, the ultrasonication time under stirring conditions is 9 min to 30 min.
[0020] In S3, the rotation speed of the stirring is 1000-1500 r / min, and the revolution speed of the stirring is 15-20 r / min.
[0021] In S3, the frequency of the ultrasound is 5 to 7 kHz.
[0022] In S3, the grinding speed is 600-650 r / min, and the grinding time is 10-15 min.
[0023] An ultra-low moisture, high wetting membrane includes: a base membrane and a coating applied to the base membrane, said coating being formed by coating with an ultra-low moisture, high wetting slurry.
[0024] In the above technical solution, the thickness of the coating is 1 to 3 μm.
[0025] The method for preparing the above-mentioned ultra-low moisture and highly wetted membrane includes: coating the ultra-low moisture and highly wetted slurry on one or both sides of a base membrane to obtain an ultra-low moisture and highly wetted membrane.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] 1. The present invention uses a mixture of boehmite fiber and carbonate for surface modification of the separator surface, which can effectively improve the separator's low moisture capacity, thereby improving its thermal stability, flame retardancy, and wettability, enhancing battery safety, thereby improving battery durability, and thus improving the driving range of new energy electric vehicles.
[0028] 2. This invention improves film performance and increases liquid absorption rate, resulting in lower package breakage rate, lower material loss, and longer shelf life of the packaging;
[0029] 3. This invention saves energy, produces more stable film quality, reduces waste, and lowers costs. Attached Figure Description
[0030] Figure 1 This is an electron microscope image of the ultra-low moisture and high wetting membrane prepared in Example 1;
[0031] Figure 2 The image shows an electron microscope image of the lithium battery separator prepared in Example 2.
[0032] Figure 3 The image shows an electron microscope image of the lithium battery separator prepared in Example 3.
[0033] Figure 4 This is an electron microscope image of the unmodified boehmite lithium battery separator prepared in Example 4;
[0034] Figure 5 This is an electron microscope image of the ultra-low moisture and highly wettable membrane prepared in Example 5. Detailed Implementation
[0035] The raw materials and their manufacturers involved in the following examples are as follows:
[0036] Boehmite fiber: Lingshou Pengshuo, the length of boehmite fiber is 200-250mm and the diameter is 3-4μm;
[0037] Granular Boehmite: Lingshou Pengshuo
[0038] Coupling agent (carbonate): Momentive;
[0039] The instruments and their model information involved in the following embodiments are as follows:
[0040] Double planetary mixer: Haojiete 30L model;
[0041] Ultrasonic equipment: Kunshan Hechuang KH2200 model;
[0042] Sand mill: Pailer rod pin type nano sand mill.
[0043] In the following examples, the base film is a PE film with a thickness of 9.44 μm.
[0044] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0045] The test method for the average liquid absorption rate in Table 3 is as follows: Cut the diaphragm into three 50mm*50mm samples (for diaphragms with a width less than 50mm, cut three full-width diaphragms with a length of 50mm, with the side length accurate to 1mm). Weigh the cut samples and record the weight as m (accurate to 0.01mg) as the mass before soaking. Soak the weighed samples in the electrolyte at room temperature for (30±1)min, remove them, and quickly place them on industrial wiping paper. Use another piece of industrial wiping paper to gently press and wipe the free electrolyte on the surface of the sample until no particulate electrolyte is visible to the naked eye. Weigh the sample and record the weight as m2 (accurate to 0.01mg) as the mass after soaking. Liquid absorption rate EU(%) = (m2-m) / m*100%. Test the liquid absorption rate of each sample in three groups and calculate the average value as the average liquid absorption rate. The separator is one of the following: the ultra-low moisture and high wetting separator prepared in Example 1; the lithium battery separator prepared in Examples 2 and 3; the surface-modified boehmite lithium battery separator prepared in Example 4; and the ultra-low moisture and high wetting separator prepared in Example 5. The electrolyte is a mixture of solvent and lithium hexafluorophosphate, with a lithium hexafluorophosphate concentration of 1.0 mol / L. The solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), with a volume ratio of 1:1:1.
[0046] Example 1
[0047] A method for preparing an ultra-low moisture, highly wettable slurry includes the following steps:
[0048] S1, Boehmite fiber is added to the reactor, and coupling agent is added at 70°C. Boehmite fiber and coupling agent are mixed and stirred for 30 minutes to obtain a semi-finished product. The semi-finished product is then filtered, dried (dried to a moisture content of 0.8 wt%), pulverized and sieved to obtain the first mixture, wherein the coupling agent is carbonate.
[0049] S2, In a double planetary mixer, the first mixture, dispersant and water are mixed and stirred for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min until uniform. In an ultrasonic device, the mixture is ultrasonicated at a frequency of 50 kHz for 10 minutes to obtain the first solution, wherein the dispersant is an ammonium salt dispersant (BASF A4040).
[0050] S3, In a double planetary mixer, the adhesive and the first solution are ultrasonically mixed for 10 minutes under stirring conditions. The rotation speed of the mixer is 1000 r / min, the revolution speed of the mixer is 20 r / min, and the frequency of the ultrasonication is 5 kHz. The mixture is then circulated and milled in a sand mill at 600 r / min for 10 minutes to obtain an ultra-low moisture, high wetting slurry. The ratio of boehmite fiber, dispersant, coupling agent, water and adhesive by mass is 24:0.1:0.04:39:3. The adhesive is a mixture of water-based polyacrylate adhesive (BM900B, purchased from Zeon, Japan) and heat-resistant polyacrylate adhesive (GR-506, purchased from Zhuzhou Gaorui) by mass, with the ratio of water-based polyacrylate adhesive to heat-resistant polyacrylate adhesive being 3:1.
[0051] A method for preparing an ultra-low moisture, highly wetted membrane includes: coating an ultra-low moisture, highly wetted slurry onto a base membrane by roller coating on one side, forming a coating layer on the base membrane, thereby obtaining an ultra-low moisture, highly wetted membrane.
[0052] Example 2
[0053] A method for preparing a lithium battery separator slurry includes the following steps:
[0054] S1, granular boehmite is added to the reactor, and a coupling agent is added at 69°C. The granular boehmite and the coupling agent are mixed and stirred for 30 minutes to obtain a semi-finished product. The semi-finished product is then filtered, dried (to a moisture content of 0.8 wt%), pulverized, and sieved to obtain the first mixture. The coupling agent is carbonate, and the average particle size of the granular boehmite is 350 nm.
[0055] S2, In a double planetary mixer, the first mixture, dispersant and water are mixed and stirred for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min until uniform. In an ultrasonic device, the mixture is ultrasonicated at a frequency of 50 kHz for 10 minutes to obtain the first solution, wherein the dispersant is an ammonium salt dispersant (BASF A4040).
[0056] S3, In a double planetary mixer, the adhesive and the first solution are ultrasonically mixed for 9 minutes under stirring conditions. The rotation speed of the mixer is 1000 r / min, the revolution speed of the mixer is 20 r / min, and the frequency of the ultrasonication is 5 kHz. The mixture is then circulated and milled in a sand mill at a speed of 600 r / min for 10 minutes to obtain a lithium battery separator slurry. The ratio of granular boehmite, dispersant, coupling agent, water and adhesive by mass is 24:0.1:0.04:39:3. The adhesive is a mixture of water-based polyacrylate binder (BM900B, purchased from Zeon, Japan) and heat-resistant polyacrylate binder (GR-506, purchased from Zhuzhou Gaorui) by mass, and the ratio of water-based polyacrylate binder to heat-resistant polyacrylate binder by mass is 3:1.
[0057] A method for preparing a lithium battery separator includes: coating a lithium battery separator slurry onto a base film on one side by roller coating, forming a coating layer on the base film, thereby obtaining a lithium battery separator.
[0058] Example 3
[0059] A method for preparing a lithium battery separator slurry includes the following steps:
[0060] S1, Boehmite fibers are added to a reaction vessel, and polycarbonate is added at 68°C. The Boehmite fibers and polycarbonate are mixed and stirred for 30 minutes to obtain a semi-finished product. The semi-finished product is then filtered, dried (to a moisture content of 0.8 wt%), pulverized, and sieved to obtain the first mixture.
[0061] S2, In a double planetary mixer, the first mixture, dispersant and water are mixed and stirred for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min until uniform. In an ultrasonic device, the mixture is ultrasonicated at a frequency of 50 kHz for 10 minutes to obtain the first solution, wherein the dispersant is an ammonium salt dispersant (BASF A4040).
[0062] S3, In a double planetary mixer, the adhesive and the first solution are ultrasonically mixed for 9 minutes under stirring conditions. The rotation speed of the mixer is 1000 r / min, the revolution speed of the mixer is 20 r / min, and the frequency of the ultrasonication is 5 kHz. The mixture is then circulated and milled in a sand mill at a speed of 600 r / min for 10 minutes to obtain a lithium battery separator slurry. The ratio of boehmite fiber, dispersant, polycarbonate, water and adhesive by mass is 24:0.1:0.04:39:3. The adhesive is a mixture of water-based polyacrylate adhesive (BM900B, purchased from Zeon, Japan) and heat-resistant polyacrylate adhesive (GR-506, purchased from Zhuzhou Gaorui) by mass, and the ratio of water-based polyacrylate adhesive to heat-resistant polyacrylate adhesive by mass is 3:1.
[0063] A method for preparing a lithium battery separator includes: coating a lithium battery separator slurry onto a base film on one side by roller coating, forming a coating layer on the base film, thereby obtaining a lithium battery separator.
[0064] Example 4
[0065] A method for preparing a boehmite lithium battery separator slurry without surface modification includes the following steps:
[0066] Step 1: In a dual planetary mixer, the dispersant, water, and granular boehmite are mixed and stirred for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min until homogeneous. Then, the mixture is sonicated at 30 kHz for 10 minutes. Next, in the dual planetary mixer, the binder is added and stirred (rotation speed of 2900 r / min, revolution speed of 20 r / min) and sonicated (ultrasonic frequency of 6 kHz) for 9 minutes to obtain a boehmite lithium-ion battery separator slurry precursor without surface modification. The ratio of dispersant, water, granular boehmite, and adhesive by mass parts is 0.1:39:24:3. The dispersant is an ammonium salt dispersant (BASF A4040), and the adhesive is a mixture of water-based polyacrylate adhesive (BM900B, purchased from Zeon Japan) and heat-resistant polyacrylate adhesive (GR-506, purchased from Zhuzhou Gaorui). The ratio of water-based polyacrylate adhesive to heat-resistant polyacrylate adhesive by mass parts is 3:1, and the average particle size of the granular boehmite is 350 nm.
[0067] Step 2: The boehmite lithium battery separator slurry precursor obtained in Step 1 without surface modification is fed into a sand mill and circulated for 10 minutes (600 r / min) to obtain the boehmite lithium battery separator slurry without surface modification.
[0068] A method for preparing a surface-unmodified boehmite lithium battery separator includes: coating a surface-unmodified boehmite lithium battery separator slurry onto a base film by roller coating, thereby obtaining a coating on the base film and obtaining a surface-unmodified boehmite lithium battery separator.
[0069] Example 5
[0070] The preparation method of an ultra-low moisture high-wetting slurry is basically the same as that of Example 1, "A preparation method of an ultra-low moisture high-wetting slurry", except that the only difference is that "the adhesive is a mixture of polyacrylate water-based adhesive (BM900B, purchased from Zeon, Japan) and polyacrylate heat-resistant adhesive (GR-506, purchased from Zhuzhou Gaorui), and the ratio of polyacrylate water-based adhesive to polyacrylate heat-resistant adhesive by mass parts is 3:1" is replaced with "the adhesive is polyacrylate adhesive (LPC-22346, purchased from BYK Chemicals)".
[0071] A method for preparing an ultra-low moisture, highly wettable diaphragm involves preparing the ultra-low moisture, highly wettable slurry from Example 5 according to the method described in Example 1, "A method for preparing an ultra-low moisture, highly wettable diaphragm".
[0072] Figure 1 This is an electron micrograph of the ultra-low moisture, high wetting membrane prepared in Example 1. Figure 2 This is an electron microscope image of the lithium battery separator prepared in Example 2. Figure 3 This is an electron microscope image of the lithium battery separator prepared in Example 3. Figure 4 This is an electron microscope image of the unmodified boehmite lithium battery separator prepared in Example 4. Figure 5 This is an electron microscope image of the ultra-low moisture, high wetting membrane prepared in Example 5. It can be clearly seen that... Figure 1 (The ultra-low moisture and highly wettable membrane prepared in Example 1) has a denser spatial structure.
[0073] The following tests were conducted using the ultra-low moisture high wetting slurry prepared in Example 1, the lithium battery separator slurry prepared in Examples 2 and 3, the surface-modified boehmite lithium battery separator slurry prepared in Example 4, and the ultra-low moisture high wetting slurry prepared in Example 5. All tests were conducted under standard atmospheric conditions (temperature 25–35°C, relative humidity 65–75%, atmospheric pressure 96–106 kPa). The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076]
[0077] As shown in Table 1, the particle size D90 of the unmodified boehmite lithium battery separator slurry prepared in Example 4 is 1.742 μm, while the particle size D90 of the ultra-low moisture high wetting slurry prepared in Example 1 is 0.932 μm, which is much smaller than the particle size of the unmodified boehmite lithium battery separator slurry prepared in Example 4. It can be seen that the ultra-low moisture high wetting slurry prepared in Example 1 (surface modified by the synergistic effect of boehmite fibers and carbonate) has a denser structure. At the same time, coating the ultra-low moisture high wetting slurry onto the base film to form an ultra-low moisture high wetting separator has a dense boehmite structure, fine particles, good dispersion, and its solid particles can be well wetted. The coating is uniform, the surface is flat, and there are no vertical scratches. Moreover, the particles are not prone to precipitation or agglomeration during storage, and the storage stability is good.
[0078] The ultra-low moisture and high wetting membrane prepared in Example 1, the lithium battery membranes prepared in Examples 2 and 3, the unmodified boehmite lithium battery membrane prepared in Example 4, and the ultra-low moisture and high wetting membrane prepared in Example 5 were tested as shown in Tables 2 and 3.
[0079] Table 2
[0080]
[0081] As shown in Table 2, the ultra-low moisture and high wettability separator prepared in Example 1 of the present invention (surface modified by the synergistic effect of boehmite fiber and carbonate) has a water content of 400 ppm, which is lower than the lithium battery separators prepared in Examples 2 and 3. This makes the ultra-low moisture and high wettability separator less prone to combustion, improves flame retardancy, and improves thermal stability.
[0082] Table 3
[0083]
[0084]
[0085] As shown in Table 3, the average liquid absorption rate of the lithium battery separator prepared in Example 2 was 148.63%, the average liquid absorption rate of the lithium battery separator prepared in Example 3 was 148.51%, while the average liquid absorption rate of the ultra-low moisture, high wettability separator prepared in Example 1 of this invention was 148.67%, which is far superior to the surface-modified boehmite lithium battery separator prepared in Example 4. The ultra-low moisture, high wettability separator prepared in Example 1 has better wettability.
[0086] In the technical solution of the present invention, the same technical effect as in Example 1 can be obtained by changing parameters such as raw material ratio, time, and temperature.
[0087] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A membrane with ultra-low moisture and high wetting capacity, characterized in that, include: A base film and a coating applied to the base film, the coating being formed by applying an ultra-low moisture, high wetting slurry, the preparation method of which includes the following steps: S1, Boehmite fiber and coupling agent are mixed at 70~75℃ and stirred for 30~35min to obtain a semi-finished product. The semi-finished product is then filtered, dried, pulverized and sieved to obtain a first mixture, wherein the coupling agent is carbonate. S2, mix the first mixture, dispersant and water, stir until uniform, and sonicate to obtain the first solution; S3, the adhesive and the first solution are ultrasonically mixed and milled under stirring conditions to obtain an ultra-low moisture high wetting slurry, wherein, by mass parts, the ratio of boehmite fiber, dispersant, coupling agent, water and adhesive is (23~25):(0.1~0.2):(0.04~0.08):(37~39):(1~3); The adhesive is a polyacrylate adhesive, which is a mixture of a water-based polyacrylate adhesive and a heat-resistant polyacrylate adhesive. The ratio of the water-based polyacrylate adhesive to the heat-resistant polyacrylate adhesive by mass is (3~6):(1~2).
2. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S2, the dispersant is an ammonium salt dispersant.
3. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S1, the drying process involves drying until the moisture content is 0.6~0.8 wt%.
4. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S2, the frequency of the ultrasound is 50~75kHz, and the duration of the ultrasound is 10~15min.
5. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S2, the rotation speed of the stirring is 3100~3600 r / min, the revolution speed of the stirring is 10~30 r / min, and the stirring time is 10~15 min.
6. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S3, the ultrasonication time under stirring conditions is 9 min to 30 min.
7. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S3, the frequency of the ultrasound is 5~7kHz.
8. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S3, the rotation speed of the stirring is 1000~1500 r / min, and the revolution speed of the stirring is 15~20 r / min.
9. The ultra-low moisture, high wetting membrane according to claim 1, characterized in that, In S3, the grinding speed is 600~650 r / min, and the grinding time is 10~15 min.
Citation Information
Patent Citations
Coated diaphragm and preparation method thereof, doping boehmite, ceramic slurry and lithium battery
CN111341982A